2016
DOI: 10.24075/brsmu.2016-05-02
|View full text |Cite
|
Sign up to set email alerts
|

The use of implants for surgical treatment of congenital diaphragmatic hernia in newborns

Abstract: Применение имплантов в коррекции диафрагмальной грыжи у новорожденныхThe use of implants for surgical treatment of congenital diaphragmatic hernia in newborns Врожденная диафрагмальная грыжа (ВДГ) -патология, которая требует обязательной хирургической коррек-ции. При значительных дефектах диафрагмы, например аплазии ее купола, зачастую возникает необходимость в использовании имплантационных материалов. До сих пор нет единой точки зрения по вопросу выбора имплан-та. В статье представлены результаты сравнительно… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Single case reports Shariff 2014, 33 Riquelme 2015, 19 Premkumar 2015, 21 Hutson 1985, 35 Gander 2010, 41 Davis 2002, 42 Cantone 2014, 25 Bruen 2007, 36 Becmeur 2001, 26 Bawazir 2019 43 22 Glick 1992, 23 Ahmed 1998 44 Retrospective case series with research questions and outcomes Yokota 2014, 27 Weaver 2006, 45 Tsai 2012, 18 Shah 2009, 46 Russel 2014, 40 Romao 2012, 14 Riehle 2007, 20 Razumovskly 2016, 11 Nasr 2010, 17 Mitchell 2008, 15 McHoney 2010, 47 Loff 2005, 7 Laituri 2010, 13 Kuklová 2011, 38 Koziarkiewicz 2014, 39 Koot 1993, 48 Kamran 2018, 49 Jawaid 2013, 9 Janssen 2018, 30 Jancelewicz 2013, 12 Grethel 2006, 5 Heiwegen 2020, 28 Guner 2008, 29 Dewberry 2019, 37 de Kort 1996, 24 D'agostino 1995, 31 Cho 2009, 50 Barnhart 2012, 16 Baerg 2012, 32 Aydin 2020 51 34 Rygl 2012, 52 Long 2019, 8 Jancelewicz 2010 6 Four studies (132 patients total) that systematically reported death rates in treated patients were included in the table. Death rates for synthetic patches ranged from 19 to 32%, whereas...…”
Section: Characteristics Of Studies Assessment Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Single case reports Shariff 2014, 33 Riquelme 2015, 19 Premkumar 2015, 21 Hutson 1985, 35 Gander 2010, 41 Davis 2002, 42 Cantone 2014, 25 Bruen 2007, 36 Becmeur 2001, 26 Bawazir 2019 43 22 Glick 1992, 23 Ahmed 1998 44 Retrospective case series with research questions and outcomes Yokota 2014, 27 Weaver 2006, 45 Tsai 2012, 18 Shah 2009, 46 Russel 2014, 40 Romao 2012, 14 Riehle 2007, 20 Razumovskly 2016, 11 Nasr 2010, 17 Mitchell 2008, 15 McHoney 2010, 47 Loff 2005, 7 Laituri 2010, 13 Kuklová 2011, 38 Koziarkiewicz 2014, 39 Koot 1993, 48 Kamran 2018, 49 Jawaid 2013, 9 Janssen 2018, 30 Jancelewicz 2013, 12 Grethel 2006, 5 Heiwegen 2020, 28 Guner 2008, 29 Dewberry 2019, 37 de Kort 1996, 24 D'agostino 1995, 31 Cho 2009, 50 Barnhart 2012, 16 Baerg 2012, 32 Aydin 2020 51 34 Rygl 2012, 52 Long 2019, 8 Jancelewicz 2010 6 Four studies (132 patients total) that systematically reported death rates in treated patients were included in the table. Death rates for synthetic patches ranged from 19 to 32%, whereas...…”
Section: Characteristics Of Studies Assessment Of Biasmentioning
confidence: 99%
“…Two studies were notable for reporting GOR outcomes for both synthetic and biological patches, rates of which were similar for both groups: Razumovskly et al demonstrated rates of 25% (from n ¼ 15) and 21% (from n ¼ 24) for synthetic and biological patches respectively, while Long et al demonstrated rates of 36% (from n ¼ 33) and 42% (from n ¼ 19) for synthetic and biological patches, respectively. 8,11 Three studies (107 patients) reporting chest wall deformity are presented, with the range of rates between 13 and 80% for synthetic patches only. The same three studies reporting scoliosis are also presented, with the range of rates between 6.1 and 40% for synthetic patches only.…”
Section: Characteristics Of Studies Assessment Of Biasmentioning
confidence: 99%